2022
DOI: 10.5194/se-13-1003-2022
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing post-Jurassic overburden in central Europe: new insights from mudstone compaction and thermal history analyses of the Franconian Alb, SE Germany

Abstract: Abstract. The Franconian Alb of SE Germany is characterized by large-scale exposures of Jurassic shallow marine limestones and dolostones, which are frequently considered to be outcrop analogues for deep geothermal reservoir rocks in the North Alpine Foreland Basin farther south. However, the burial history of the Franconian Alb Jurassic strata is not well known as they were affected by emersion, leading to extensive erosion and karstification with only remnants of the original Cretaceous and Cenozoic cover ro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 88 publications
0
2
0
Order By: Relevance
“…7 a, b; Supplementary material Table 3). MICP is restricted to pore throats > ~ 3 nm compared to 1.2 nm in the case of He-pycnometry (Freitag et al 2022 ) which results in the observed systematic shift in detectable porosity. Both Φ MICP and Φ He show decreasing trends with depth, with the shallower Pannonian samples exhibiting the highest and the deepest Badenian samples exhibiting the lowest porosity values for each method.…”
Section: Resultsmentioning
confidence: 99%
“…7 a, b; Supplementary material Table 3). MICP is restricted to pore throats > ~ 3 nm compared to 1.2 nm in the case of He-pycnometry (Freitag et al 2022 ) which results in the observed systematic shift in detectable porosity. Both Φ MICP and Φ He show decreasing trends with depth, with the shallower Pannonian samples exhibiting the highest and the deepest Badenian samples exhibiting the lowest porosity values for each method.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of lithofacies, the Malm β carbonates in South Germany predominantly classify as mud-to wackestones (Koch et al 2005). These units of which maximum burial depth of c. 1100 m has been recently determined represent an excellent opportunity to acquire and compare petrophysical macro-and microstructural parameters of reservoir analogs to geothermal target lithologies in the Munich area of the SGMB 100-200 km to the south, where a similar burial depth was reached (Freitag et al 2022). From a number of available natural and artificial outcrops we chose a study area NE of Nuremberg (Fig.…”
Section: Introductionmentioning
confidence: 99%